2015
DOI: 10.12738/estp.2015.1.2242
|View full text |Cite
|
Sign up to set email alerts
|

Interest in Birds and its Relationship with Attitudes and Myths: A Cross-cultural Study in Countries with Different Levels of Economic Development

Abstract: Birds are one of the most important species that can help protect biodiversity. Although birds are important beings for biodiversity and human existence, there is a relatively less quantity of research that has investigated the interest in and attitudes toward birds. This study aims to investigate the knowledge level of and attitudes toward birds among students in countries at different levels of economic development. To collect the data, a Bird Knowledge Questionnaire and a Bird Attitude Questionnaire were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 57 publications
2
11
1
Order By: Relevance
“…Caller profile appeared to be significant, with men more likely to report a bird than women. In contrast, a previous study found that women appeared to have a greater interest in birds then men, though there was no significant difference in knowledge about local species (Hummel et al 2015). Caller age was also significant, with callers ages more likely to fall within the "21-40" and "41-60" categories, in addition to callers being likely to have higher salaries.…”
Section: Discussioncontrasting
confidence: 74%
“…Caller profile appeared to be significant, with men more likely to report a bird than women. In contrast, a previous study found that women appeared to have a greater interest in birds then men, though there was no significant difference in knowledge about local species (Hummel et al 2015). Caller age was also significant, with callers ages more likely to fall within the "21-40" and "41-60" categories, in addition to callers being likely to have higher salaries.…”
Section: Discussioncontrasting
confidence: 74%
“…Additionally, attitudes toward nature and animals were significantly related to species knowledge [1]. Participation in animal-related activities showed a strong association with interest in animal species [9]. Palmberg et al [6] and Cox and Gaston [26] similarly observed a positive correlation in their respective studies.…”
Section: Introductionmentioning
confidence: 88%
“…In the kindergarten age, Randler and Wieland [19] found no difference between boys and girls in species knowledge. In a study by Hummel et al [9] based on 852 schoolchildren (average age 11.48 years) from different countries (Colombia, Germany, Slovakia, and Turkey) female participants showed a greater interest in ornithology, but there was no difference in the cognitive domain. Other studies in adolescents found that boys in the UK had significantly greater wildlife knowledge than girls [14].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This result appears to be a reflection of the differences in preferences and attitudes toward wildlife (e.g., insects) between the genders; men are more likely to favor wildlife than women [39,61,63]. However, since the magnitude of gender differences in preferences/attitudes toward wildlife might depend on cultural and the socio-economic context [64], additional studies are needed to understand more fully the role of gender in determining the intensity of nature-based education.…”
Section: Effects Of Other Personal Factorsmentioning
confidence: 99%